Analisis Kebijakan Batas Usia Pensiun PNS Dalam UU No.5 Tahun 2014 Tentang Aparatur Sipil Negara - Argo Pambudi; Joko Kumoro (Telaah Bisnis, 2016)
AbstractThis research is motivated by a deep desire of understanding the changes of policy content of the Limit of Retirement Age of civil servants in the Government of the city of Yogyakarta. Substantive analysis of this research focused on the acceptability of the regulation of the Limit Age of Retirement. The purpose of this study is to contribute to the empowerment of the state apparatus through a intensification of existing civil servants, preventing civil servants who are still productive to leave the bureaucratic structure in earlier - which means a waste of state finances - and to propose alternative arrangements of future policy of retirement age for civil servants. The research method used in this study is a Mixed Methods Analysis, which is a combination of both Survey Method with Qualitative Descriptive research methods. Informants and respondents of this study is the structural and functional officials in the city government that is actually involved in the problems associated with the implementation of this regulatory changes. The results of this research showed that most civil servants who was observed received this new rules, but from the perspective of the municipal government organization this policy raises a number of internal problems, especially problems related to fulfilment structural positions pertaining with limited in number of the existing number of civil servants.